Analisis Karakteristik Crackers Hasil Substitusi Tepung Terigu Dengan Tepung Ampas Tahu - Nurul Charismawaty Sabir; Lahming Lahming; Andi Sukainah (Universitas Negeri Makassar, 2020)
This study aims to determine the chemical quality and organoleptic level of panelist acceptance of crackers resulting from the substitution of wheat flour with tofu dregs flour. This research is a quantitative research with an experimental approach. This study uses a Completely Randomized Design (CRD) with four treatments with the ratio of wheat flour and tofu dregs flour, namely 100%:0%, 75%:25%, 50%:50%, and 25%:75% with 3 repetitions. This research was carried out in two stages. The first stage is making tofu dregs flour and then the second stage is making crackers. The variables observed in this study were chemical tests which included water content, ash content, protein, carbohydrates, crude fiber and organoleptic tests. Data were processed using SPSS version 21, with the method of analysis of variance (ANOVA) and continued with the DMRT test (Duncan). The results showed that the addition of tofu dregs flour gave effect to the crackers produced, so that the best treatment was found, namely treatment A with a composition of 75% wheat flour and 25% tofu dregs flour.